Dynac Visitor Management System with Facial Recognition - Abd Hafiff, Abdul Hazim; Ahmad Khalid, Shamsul Kamal (Applied Information Technology And Computer Science, 2023)
This paper presents the development of a computerized visitor management system with facial recognition for Dynac Sdn Bhd. The existing manual paper-based registration system has led to some human errors and inefficiencies. The proposed system integrates a facial recognition function to increase efficiency when checking-in and checking-out visitors. It includes digitalizing the registration form, utilizing a web camera for face recognition, and implementing security measures. The web-based system manages to improve the registration efficiency, streamlined visitor management, and enhance security. The system still has some room for improvement such as expanding the visitor classification, implementing additional notification methods and faster facial recognition engines. This system significantly improves visitor management and enhances the overall visitor experience. Several experiments have been conducted with the target users.  The system passed all (100%) security checklist planned for the system including user, visitor management and system trail logs.